New find of Diarthrognathus (Therapsida: Cynodontia) after seventy years - Gow, Chris E (Bernard Price Institute for Palaeontological Research, 1994)
Diarthrognathus is arguably South Africa's most famous therapsid fossil. Since its discovery seventy years ago no new material had come to light until now. This paper records the recovery, from the Elliot Formation of South Africa, of a partial left lower dentary with most of its dentition preserved.
Keywords: Therapsida; Ictidosauria; Tritheledontidae